Influence of CEO Characteristics on Accounting Information Disclosure Quality—Based on the Mediating Effect of Capital Structure. Issue 8 (20th June 2020) - Lin, Ping; Lin, Boqiang; Lei, Fu
ABSTRACT: Taking the A-share listed companies of the Shenzhen Stock Exchange in 2012–2017 as a sample and capital structure as a moderator variable, this paper uses a mediating effect model to investigate the mechanism of influence of CEO characteristics on accounting information disclosure quality (IDQ). According to our findings, female CEOs and CEO's educational level negatively influence IDQ, while CEO's wage level and the separation between CEO and chairman positively influence IDQ. CEO's educational level positively influences the capital structure; CEO's wage level and the separation between CEO and chairman negatively influence the capital structure, while female CEOs have a non-significant influence on it. Further investigation reveals that, in the mechanism of influence of female CEOs on IDQ, and the influence of CEO's educational level on IDQ, capital structure exerts no mediating effect; and that, in the mechanisms of influence of CEO's wage level, and the separation between CEO and chairman on IDQ, capital structure exerts a partial mediating effect. On this basis, this paper offers methodological inspiration and theoretical support to perfect the governance of Chinese listed companies and regulate their market behaviors.